Pengenalan Digitalisasi Di SDN Sanggrahan 1 Kelurahan Sanggrahan, Kecamatan Grogol, Kabupaten Sukoharjo - Riris Wahyuning Tias; Umi Nur Solikah; Nabila Rizkiani; Wanda Inggrit Pramesti (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2023)
With the low level of technology and information knowledge at SDN Sanggrahan 1, we hereby provide training in the Microsoft Office Application Introduction Program (Microsoft Word) to students. Computer application training for grade 6 children This service activity aims to provide experience and understanding and assistance to children in Microsoft word training. The method used in this training activity is material explanation, question and answer and practice. The expected result of this training is to increase the quality of children's knowledge related to computer applications so that it can make it easier for them to do computer-based school assignments. This activity received a good response from various parties, especially students, they were happy with this training because it was considered very helpful for them in completing computer-based school assignments. From this activity we can conclude that this training succeeded in improving students' ability to apply Microsoft Office.